Thrombotic microangiopathy as a presentation of undifferentiated metastatic carcinoma, a case report - Pereira, Filipa Margarida Ferreira; Costa, Ana Elisa; Silva, Margarida Freitas (European Journal of Oncology and Environmental Health, 2019)
Thrombotic microangiopathy (TMA) is a group of hereditary or acquired syndromes that shared clinical and pathological characteristics: microvascular thrombosis, thrombocytopenia and ischaemic end-organ damage. Thrombotic microangiopathy can be a manifestation of a subjacent disease as cancer, infection, auto-immune disease and others. Patients presenting cancer-related TMA have an extremely poor prognosis. We report a case of a 61-year-old man who was admitted for persistent lumbar pain. Results from imagiological exams showed multiple retroperitoneal lymph nodes suggestive of metastatic cancer. A sudden clinical episode with changes in mental and behavioral status and laboratory alterations consistent with TMA, were observed. A first strategy including plasma exchange and steroids was performed with no clinical response. The retroperitoneal lymph node biopsy revealed undifferentiated carcinoma of unknown primary and then, chemotherapy was started.